Toán Lớp 8: 6 (a+b) ^3=a^3+b^3+3ab (a+b) 7 (a – b) ^3= a^3-b^3+3ab(a-b) 8 x^3-y^3+xy(x-y)=(x-y) (x+y)^2 9 x^3+y^3-xy(x+y) = (x+y) (x-y)^2

Question

Toán Lớp 8: 6 (a+b) ^3=a^3+b^3+3ab (a+b)
7 (a – b) ^3= a^3-b^3+3ab(a-b)
8 x^3-y^3+xy(x-y)=(x-y) (x+y)^2
9 x^3+y^3-xy(x+y) = (x+y) (x-y)^2, hướng dẫn giải giúp em bài này ạ, em cảm ơn thầy cô và các bạn nhiều.

in progress 0
Kiều Nguyệt 1 tháng 2022-12-20T23:44:17+00:00 2 Answers 0 views 0

TRẢ LỜI ( 2 )

  1. #Sad
    → \text{Chứng minh:}
    6)
    (a+b)^3 = a^3+b^3+2ab(a+b)
    \text{·Ta có:}
    VT = (a+b)^3
    = a^3+3.a^2b+3.a.b^2+b^3
    = (a^3+b^3)+(3a^2b+3ab^2)
    = (a^3+b^3)+3ab(a+b) = VP \text{(→đpcm)}
    7)
    (a-b)^3 = a^3-b^3+3ab(a-b)
    \text{·Ta có:}
    VT = (a-b)^3
    = a^3-3.a^2b+3.ab^2-b^3
    = (a^3-b^3)+(-3a^2b+3ab^2)
    = (a^3+b^3)+3ab(-a+b)
    = (a^3+b^3)+3ab(b-a) = VP \text{(→đpcm)}
    8)
    x^3-y^3+xy(x-y) = (x-y)(x+y)^2
    \text{·Ta có:}
    VT = x^3-y^3+xy(x-y)
    = (x-y)(x^2+xy+y^2)+xy(x-y)
    = (x-y)(x^2+xy+y^2+xy)
    = (x-y)(x^2+2xy+y^2)
    = (x-y)(x+y)^2 = VP \text{(→đpcm)}
    9)
    x^3+y^3-xy(x+y) = (x+y)(x-y)^2
    \text{·Ta có:}
    VT = x^3+y^3-xy(x+y)
    = (x+y)(x^2-xy+y^2)-xy(x+y)
    = (x+y)(x^2-xy+y^2-xy)
    = (x+y)(x^2-2xy+y^2)
    = (x+y)(x-y)^2 = VP \text{(→đpcm)}
     

  2. ***Lời giải***
    6)
    Chứng minh: (a+b) ^3=a^3+b^3+3ab (a+b)
    Ta có: (a+b) ^3=a^3+3a^2b+3ab^2+b^3
    =a^3+b^3+(3a^2b+3ab^2)
    =a^3+b^3+3ab(a+b)
    Vậy (a+b) ^3=a^3+b^3+3ab (a+b)
    7)
    Chứng minh: (a – b) ^3= a^3-b^3+3ab(b-a)
    Ta có: (a – b) ^3=a^3-3a^2b+3ab^2-b^3
    =a^3-b^3+(-3a^2b+3ab^2)
    =a^3-b^3+3ab(b-a)
    Vậy (a – b) ^3= a^3-b^3+3ab(b-a)
    8)
    Chứng minh: x^3-y^3+xy(x-y)=(x-y) (x+y)^2
    Ta có: (x-y) (x+y)^2=(x-y) (x+y)(x+y)
    =(x^2-y^2)(x+y)
    =x^2(x+y)-y^2(x+y)
    =x^3+x^2y-xy^2-y^3
    =x^3-y^3+(x^2y-xy^2)
    =x^3-y^3+xy(x-y)
    Vậy x^3-y^3+xy(x-y)=(x-y) (x+y)^2
    9)
    Chứng minh: x^3+y^3-xy(x+y) = (x+y) (x-y)^2
    Ta có: (x+y) (x-y)^2=(x+y)(x-y)(x-y)
    =(x^2-y^2)(x-y)
    =x^2(x-y)-y^2(x-y)
    =x^3-x^2y-xy^2+y^3
    =x^3+y^3+(-x^2y-xy^2)
    =x^3+y^3-xy(x+y)
    Vậy x^3+y^3-xy(x+y) = (x+y) (x-y)^2

Leave an answer

Browse

12:2+4x4-12:2-5x3 = ? ( )